Local Government Policy Evaluation Assessment in Domestic Waste Management (Case Study Approach to Evaluation of Road Sweep Service Performance in Kediri, Indonesia) - Pujowati, Yenik (Udayana Journal of Social Sciences and Humanities; Vol 5 No 2 (2021): UJoSSH, September 2021DO - 10.24843/UJoSSH.2021.v05.i02.p02, 2021)
This study aims to determine government policies in domestic waste management carried out in the city of Kediri and evaluate the implementation of performance policies for domestic waste management in the city of Kediri. Based on law No.18 of 2008 concerning waste management, and the policy of regional regulation No.3 of 2015 concerning waste management in the city of Kediri. Based on these regulations, it is very important to strengthen the performance of the service officers in the road sweep in the city of Kediri. The research method used is a qualitative research method. Data is obtained through observation and analysis of secondary data, as well as primary data. The results of this study indicate that under the service performance indicators of street sweepers in Kediri City are still not efficient and road sweeping technical work is still not productive. The results of the study can be concluded based on local government policies in improving the performance of road sweeping services in the City of Kediri so that the performance of road sweeping officers is more optimal, then the Government of Kediri City is recommended to make standard operating procedures (SOP) for road sweeping officers in Kediri City.